Cost effectiveness of routine histology for haemorrhoidectomy specimens - Watter, Henry K.; Ng, Guat Shi; Nalliah, Sasikaran (International Surgery Journal, 2021)
Background: Routine histology for haemorrhoidectomy specimens remains commonplace in clinical practice, as a method of detecting incidental anal cancer. However, its utility and cost-effectiveness is unclear in the literature. This study aimed to determine the cost-effectiveness of routine histology for haemorrhoidectomy specimens in a regional Australian hospital. The secondary aim was to determine the proportion of specimens sent for histology, and whether individual surgeons had a statistically significant preference for whether to send for histology. Methods: This was a retrospective cohort study of patients who received haemorrhoidectomies at Hervey Bay Hospital between March 2012 and May 2020. Cost effectiveness of routine histology was investigated by weighing the number of incidental anal cancers detected against the cost of analysis. The proportion sent for histology was determined, both as a whole and by individual consultant surgeons. Results: Routine histology was ordered in 65% of patients who received haemorrhoidectomies over the study period (n=119), costing 13,623 AUD (1,651 AUD per year). No cases of incidental anal dysplasia or neoplasia were found. Only 1 of the 8 most prolific surgeons over the study period demonstrated a statistically significant preference for whether to send for histology. Conclusions: Our study does not support routine histology for haemorrhoidectomy specimens as a cost-effective practice for detecting incidental anal cancer. Most individual surgeons did not display a clear preference for whether to send for histology.